1049 IMPROVING TELEPHONE COMMUNICATION WITH FAMILIES ON A BUSY MEDICAL WARD DURING THE PANDEMIC. (14th June 2022) - Cohen, S; Singh, R; Aldawoodi, R; Sukhnani, M; Munavvar, R; Topiwala, U; Beckett, H; O'Kelly, K
Abstract: During the pandemic it became critical to reduce visiting to only very specific situations. This resulted in an increase of complaints where a lack of communication from the ward had been recognised as a theme, in spite of the fact that many doctors spent a great deal of time providing updates over the phone to patient's families. It was noted there were a number of inefficiencies with respect to communicating with families; some families were being contacted repeatedly whereas others were struggling to get in touch. Chronic staffing shortages were also a barrier to effective and timely communication. Qualitative data collected via an online survey demonstrated that junior doctors valued the importance of communicating with families, particularly to provide clinical updates or obtain collateral histories, but found that the extra burden created by the pandemic resulted in far less time to do this efficiently and often resulted in time management difficulties. We introduced a strategy, by way of a magnetic communication board, that provided a flexible, at-a-glance method of ensuring all families had received regular updates from the medical team and collateral histories had been obtained for all relevant patients. We collected weekly data regarding the number of interactions between the medical team and patient relatives' as a percentage of the total number of bed spaces. An overall improvement was noted: 67% pre-intervention to 76% post, with a maximum of 88% during one particularly successful week. We also were able to demonstrate an increase in ReSPECT form completion (from 40% to 65%). The introduction of an organisational tool such as our communication board resulted in improved patient and relatives' satisfaction; and an improvement in team performance and overall time management. We are now aiming to build on this and roll it out during the next wave of the pandemic.